Answer:
P(x) = - 7x² + 12
Step-by-step explanation:
Given zeros x = 2, x = - 2, x = , x = -
Then the factors are (x - 2), (x + 2), (x - ), (x + )
and the polynomial is the product of the factors, that is
P(x) = (x - 2)(x + 2)(x - )(x + ) ← expand in pairs using FOIL
= (x² - 4)(x² - 3) ← distribute
= - 3x² - 4x² + 12 ← collect like terms
= - 7x² + 12
<span>Susanne is 16 years old.</span>
b = Bob's age
s = Susanne's age
d = Dakota's age
Bob's age is 4 times greater than Susanne's age:
b = 4s
Dakota is three years younger than Susanne:
d = s - 3
The sum of Bob's, Susanne's, and Dakota's ages is 93:
b + s + d = 93
solve these equations:
b = 4s
d = s - 3
b + s + d = 93
and get:
b = 64 years
s = 16 years
(remember that s = Susanne)
d = 13 years
Let x = amount invested at 8%
26000 - x = amount invested at 6%
0.08x + 0.06(26000 - x) = 1860
solving the equation you get x = 15000
and subtract that from 26000 you get 11000
8% investment = 15000
6% investment = 11000
Answer:
answer is 3
Step-by-step explanation:
n+1=3+2/2=3
The number is 3 and it is a odd number.
I hope it's helpful!
At x=2, y=4
At x=4, y=16
So the total change in y from x=2 to x=4 is 16-4=12
And since average rate of change = total change in y divided by total change in x within the same period, therefore the answer is 12/2 = 6
Hope that helps. Let me know if you have any questions.